1999
DOI: 10.1094/cchem.1999.76.2.308
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of Flours that Relate to Sorghum Couscous Quality

Abstract: Cereal Chem. 76(2):308-313Flours from eight sorghum cultivars were evaluated for their couscousmaking ability with the objective of finding predictive relationships between flour physicochemical properties and couscous quality. Chemical composition, physical characteristics, and pasting and gelatinization properties of the flours were determined. A laboratory procedure was used to prepare couscous. Couscous properties were evaluated and compared to a laboratoryprepared and a commercial durum wheat couscous. Ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 7 publications
4
31
0
Order By: Relevance
“…Pasting properties of sorghum flour are a key to understanding the physical characteristics and potential utilization. Aboubacar and Hamaker (1999), and Akingbala and Rooney (1987) reported differences among sorghum cultivars and an apparent association of amylose con- tent with peak viscosity using a Brabender Visco-Amylograph. Our results confirmed differences due to seedlot (Table 1), but because of significant kernel sizeÂseedlot interactions, gave no consistent evidence that particular RVA pasting properties can be attributed to kernel size.…”
Section: Rapid Visco Analyzer Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pasting properties of sorghum flour are a key to understanding the physical characteristics and potential utilization. Aboubacar and Hamaker (1999), and Akingbala and Rooney (1987) reported differences among sorghum cultivars and an apparent association of amylose con- tent with peak viscosity using a Brabender Visco-Amylograph. Our results confirmed differences due to seedlot (Table 1), but because of significant kernel sizeÂseedlot interactions, gave no consistent evidence that particular RVA pasting properties can be attributed to kernel size.…”
Section: Rapid Visco Analyzer Measurementsmentioning
confidence: 99%
“…In sorghum, grain hardness is the most important and consistent characteristic that affects porridges (Rooney, Kirleis, & Murty, 1986). Aboubacar and Hamaker (1999) reported that hard sorghum grain produced flours containing a high proportion of coarse particles with low ash and high damaged starch content and yielded a higher proportion of desirable sorghum couscous granules.…”
Section: Introductionmentioning
confidence: 99%
“…White colored grain sorghum varieties from tan type plants yielded the best couscous product (Galiba et al 1988 ). Couscous quality depends upon the size uniformity, color, stickiness and mouth-feel of the product (Aboubacar and Hamaker 1999 ).…”
Section: Traditional Pattern Of Sorghum Food Consumption In Africa Anmentioning
confidence: 99%
“…Grain hardness in sorghum has been related to quality in several food products. Grain hardness has been found to influence the cooking quality of pearled sorghum (Cagampang and Kirleis 1984), sorghum porridge (Rooney et al, 1986), couscous quality (Aboubacar and Hamaker 1999) and sorghum bread quality (Schober et al, 2005). Grain hardness has also been reported to play a role in the milling quality of sorghum (Maxson et al, 1971, Munck et al, 1981, Munck 1995, Rooney and Waniska 2000 and is related to mold susceptibility and resistance in sorghum breeding lines (Jambunathan et al, 1992;Menkir et al, 1996b).…”
Section: Physical Propertiesmentioning
confidence: 99%